Pengembangan Sistem Informasi Siklus Pendapatan pada PT XYZ (Pendekatan Studi Kasus) - Yohannes Kurniawan; Janastasha Christie Parapaga (ULTIMA InfoSys, 2014)
The research goal is to identify and analyze the need of accounting information system related to the revenue cycle at PT XYZ. This paper designing the useful of accounting information systems to support the current business processes, especially on the revenue cycle process. The design method is an Object Oriented Analysis and Design (OOAD) which refers to the modeling and design requirements discipline. And the result achieved by analysis and design of accounting information systems can support current activities of the revenue cycle, especially for the documentation and store of transaction data, and generate reports in accordance with company requirements. Conclusions derived from the analysis and design is the implementation of a webbased application that can help PT XYZ to do the work in different places, such as marketing office, head office and especially at the exhibition. Index Terms - Accounting Information System, revenue cycle, OOAD